2021
DOI: 10.3390/w13141946
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Shallow Groundwater Purification Processes after the Construction of a Municipal Sewerage Network

Abstract: In the present study, the impact of the construction of the sewerage network (2014) on groundwater quality was studied on the example of a middle-sized settlement in the Great Hungarian Plain and changes in water quality were assessed using GIS and multivariate statistical analysis. As a result of the pollution that has been going on for decades, the groundwater supply of the municipality has become heavily polluted. In the period before sewerage (2011–2013), clear spatial differences were shown in the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Meanwhile, areas characterized as Medium vulnerability, in general, presented aquifers of the type of free, lithology of types of medium sand, thin and very sand (preponderantly) and clayey sand soil (to a lesser extent), as well as the distance from the top to the water table between 5 and 20 meters. In fact, pollutants can more easily pass through permeable rock and contaminate groundwater (Mester et al, 2021). Furthermore, it is observed that the High vulnerability areas present the same features of confinement degree and lithology as the Medium vulnerability areas, being distinguished from the last ones due to the parameter D; where the distance from the top to the water table in these areas was a maximum of 5 meters.…”
Section: /11mentioning
confidence: 98%
“…Meanwhile, areas characterized as Medium vulnerability, in general, presented aquifers of the type of free, lithology of types of medium sand, thin and very sand (preponderantly) and clayey sand soil (to a lesser extent), as well as the distance from the top to the water table between 5 and 20 meters. In fact, pollutants can more easily pass through permeable rock and contaminate groundwater (Mester et al, 2021). Furthermore, it is observed that the High vulnerability areas present the same features of confinement degree and lithology as the Medium vulnerability areas, being distinguished from the last ones due to the parameter D; where the distance from the top to the water table in these areas was a maximum of 5 meters.…”
Section: /11mentioning
confidence: 98%
“…Such leakage can facilitate the infiltration of pollutants into soil and groundwater, posing a potential hazard to water quality. Therefore, efficient development and maintenance of sewer networks are imperative not only to uphold environmental integrity, but also to safeguard groundwater reservoirs [4][5][6]. In the field of construction, as in many other sectors, the use of Environmental Product Declarations in construction regulations is still in its early stages in most EU countries.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the potential pollution of groundwater resulting from organic and inorganic pollutants, a statistical approach is used. Research concerning the analysis of anions and cations content, whether through an integrated approach or the assessment of the sewerage network construction impact on groundwater quality, uses statistical tools, such as Principal Components Analysis, Discriminant Analysis, or Cluster Analysis [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%